2012
DOI: 10.7589/0090-3558-48.3.835
|View full text |Cite
|
Sign up to set email alerts
|

Road-killed Common Toads (Bufo bufo) in Flanders (Belgium) Reveal Low Prevalence of Ranaviruses and Batrachochytrium dendrobatidis

Abstract: ABSTRACT:Road-killed common toads (Bufo bufo; n51,740) from Flanders, Belgium, were tested for ranavirus and Batrachochytrium dendrobatidis (Bd) using polymerase chain reaction. Both infections were present at a very low prevalence (,0.2% with a confidence interval of 95% for ranavirus and 0.63% for Bd).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Presence preceding 1999 cannot be excluded because fixation history was not known for all specimens, and some may have been originally fixed in formalin, which reduces the chance of detecting Bd (Soto‐Azat et al ). Although mass mortality events in amphibians do occur in our study area, none have been attributed to chytridiomycosis (Kik et al ; Martel et al , ). Hypotheses explaining the observed pattern of infection and lack of severe costs associated with Bd presence include the fungus is endemic and either exhibits reduced virulence or host species exhibit increased tolerance or resistance or Bd is recently arrived but has yet to firmly establish or reach a critical threshold where more detectable costs to hosts can be detected.…”
Section: Discussionmentioning
confidence: 76%
“…Presence preceding 1999 cannot be excluded because fixation history was not known for all specimens, and some may have been originally fixed in formalin, which reduces the chance of detecting Bd (Soto‐Azat et al ). Although mass mortality events in amphibians do occur in our study area, none have been attributed to chytridiomycosis (Kik et al ; Martel et al , ). Hypotheses explaining the observed pattern of infection and lack of severe costs associated with Bd presence include the fungus is endemic and either exhibits reduced virulence or host species exhibit increased tolerance or resistance or Bd is recently arrived but has yet to firmly establish or reach a critical threshold where more detectable costs to hosts can be detected.…”
Section: Discussionmentioning
confidence: 76%
“…B. dendrobatidis is currently present almost everywhere amphibians occur [ 7 ]. Until 2010, in Northern Europe it occurred in amphibian populations in a coexistence steady state [ 8 , 9 ], with only rare reports of B. dendrobatidis -linked mortality [ 10 , 11 ]. Starting from 2010, a steep enigmatic decline was observed in an endangered but stable population of fire salamanders ( Salamandra salamandra ) in the south of the Netherlands [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, substantial opportunity exists for Bd for introduction into Speleomantes populations and to amplify rapidly once introduced, but neither of these seems to have occurred to any significant degree. Field studies of other amphibian species have reported low prevalence or absence of detectable infection in species that show seasonal fluctuations in prevalence 3537. We find this an unlikely explanation for the observed absence of infection.…”
Section: Discussionmentioning
confidence: 46%